Intercultural Communication of Local Buyers in Business Negotiation Practices with Mask Artisans - Adz Dzikrya Syainie; Inggit Nurrohmah; Dian Andriany; Sri Wulandari (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
WAS Gallery is an art gallery located in Slangit Village, Cirebon Regency, which specializes in producing various traditional crafts, particularly Cirebon masks, and has successfully reached the national market with customers across different regions of Indonesia. This study aims to further explore the communication strategies employed by consumers and the outcomes of intercultural communication in the business negotiation process between WAS Gallery and clients from diverse regions. The research was conducted at WAS Gallery in Slangit Village, Klangenan District, Cirebon Regency, West Java, using a qualitative descriptive method through interviews, documentation, observation, and literature review as data collection techniques. The study is grounded in Gudykunst’s theory of intercultural communication, which includes four key indicators: cultural, sociocultural, psychocultural, and environmental. The findings reveal that these four indicators significantly influence mutual respect and tolerance among individuals, recognizing that each person brings different cultural backgrounds that shape their communication styles. This research is expected to help both artisans and customers enhance trust and mutual appreciation for each other's cultures.